Different prevalence and spectrum of malignancy between Chinese patients and American patients with rheumatoid arthritis: a comparative study - Zhi-Ming Ouyang; Yao-Wei Zou; Jie Pan; Ye Lu; Ying Yang; Qian-Hua Li; Jian-Da Ma; Pei-Wen Jia; Tao Wu; Yu-Ting Fan; Jian-Zi Lin; Xiu-Ning Wei; et al. (PeerJ)
Objective To characterize the epidemiological characteristics of malignancy in Chinese patients with rheumatoid arthritis (RA) versus American patients and investigate their associated factors. Methods Data were collected from a real-world Chinese RA population and American patients with RA from the National Health and Nutritional Examination Survey. The prevalence and subtypes of malignancy and their potential associated factors were investigated in both populations. Results A total of 2,073 Chinese and 2,928 American patients with RA were included. There was a lower prevalence of malignancy in Chinese than in their American counterparts before (5.7% vs. 17.1%) and after matching (6.2% vs. 12.6%, both P < 0.001). Gender discrepancies in malignancy prevalence were observed, with a male predilection for RA with malignancy in China (8.2% vs. 5.5%), while it was the opposite in American patients (10.1% vs. 13.5%, both P < 0.05). The top type of malignancy among male patients with RA was lung cancer in Chinese (2.29%), but non-melanoma skin cancer (3.43%) in American; while among female patients was breast cancer both in Chinese (1.72%) and American (3.43%). Multivariate logistic regression analyses showed that older age (odds ratio (OR) = 1.050) and positive anti-cyclic citrullinated peptide antibody (OR = 2.752) were independently associated with malignancy in Chinese patients with RA, while female (OR = 1.395), older age (OR = 1.033), active smoking (OR = 1.580) and cardiovascular diseases (OR = 1.523) in American patients. Conclusion The prevalence, subtypes and risk factors of malignancy were substantially different in Chinese patients with RA and their American counterparts, which implied the importance of individualized malignancy screening strategies for patients with RA.